The big book of hacks. (Weldon Owen, 2016)
In this reboot of the popular 2012 title, readers will find a collection of the most up-to-date and thrilling DIY tech projects around -- straight from the experts at Popular Science magazine. Updated with new and more modern projects, the Big Book of Hacks the perfect book for aspiring makers, curious young techies and old-school enthusiasts alike ... especially any who love using a soldering iron! Charge up that drill, fire up your soldering iron, and get ready to hack! Starting with a robust introduction to basic yet essential maker skills and followed by four comprehensive chapters of hack projects, this book has everything youll need.